PENGARUH KOMPETENSI DAN PELUANG SUKSES TERHADAP PEMBERDAYAAN KARYAWAN PADA KEPEMIMPINAN TRANSFORMASIONAL - Linawati Linawati (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
This research is intended to analyze the influence of competency and chances of success on the empowerment of employee based on syncretical model of charismatic/ transformational leadership.The respondents consist of 52 employees of PT. Angkasa Pura I Adisutjipto International Airport, Yogyakarta. Questionnaire are used to collect data from the respondents. The instrument of questionnaire from Behling and McFillen are used to measures the variable of competency, chances of success, and empowerment. The data were analized by Multiple Regression Analysis. The result of the study indicate that: (i) competency and chances of success has positive significant influence on the empowerment of employee, (ii). competency has no dominant influence on the empowerment of employee.